In silico identification, synthesis and biological evaluation of novel tetrazole inhibitors of MurB. (12th February 2018) - Hrast, Martina; Jukič, Marko; Patin, Delphine; Tod, Julie; Dowson, Christopher G.; Roper, David I.; Barreteau, Hélène; Gobec, Stanislav
Abstract : In the context of antibacterial drug discovery resurgence, novel therapeutic targets and new compounds with alternative mechanisms of action are of paramount importance. We focused on UDP‐ N ‐acetylenolpyruvylglucosamine reductase (i.e. MurB), an underexploited target enzyme that is involved in early steps of bacterial peptidoglycan biosynthesis. On the basis of the recently reported crystal structure of MurB in complex with NADP +, a pharmacophore model was generated and used in a virtual screening campaign with combined structure‐based and ligand‐based approaches. To explore chemical space around hit compounds, further similarity search and organic synthesis were employed to obtain several compounds with micromolar IC50 values on MurB. The best inhibitors in the reported series of 5‐substituted tetrazol‐2‐yl acetamides were compounds13, 26 and30 with IC50 values of 34, 28 and 25 μm, respectively. None of the reported compounds possessed in vitro antimicrobial activity against Staphylococcus aureus and Escherichia coli . Abstract : Combined ligand‐based and structure‐based approaches were used in MurB inhibitor design. Model based on crystal structure of MurB in complex with NADP + was used in a virtual screening campaign to identify a tetrazole hit compound. Chemical space around the hit compound was further explored to encompass novel inhibitors of Escherichia coli MurB displaying IC50 values from 25 to 34 μm .